2022
DOI: 10.1101/2022.06.22.22276787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved SARS-CoV-2 neutralization of Delta and Omicron variants of concern after fourth vaccination in hemodialysis patients

Abstract: Background Hemodialysis patients are exposed to a markedly increased risk when infected with SARS-CoV-2. To date it is unclear if hemodialysis patients benefit from a fourth vaccination. Methods A total of 142 hemodialysis patients (median age 72.6 years, 33.8% female) received four COVID-19 vaccinations between December 2020 and March 2022. RDB binding antibody titers were determined in a competitive surrogate neutralization assay. Vero-E6 cells were infected with SARS-CoV-2 variants of concern (VoC) Delta (B… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Our study is, to our knowledge, the only study examining the longitudinal humoral and cellular immune response towards the most recent SARS-CoV-2 isolates in haemodiaylsis patients after administration of consistent vaccination regimens starting with a triple dose of BNT162b2 followed by a fourth full-dose of mRNA-1273. Whilst other studies principally support the beneficial impact of a fourth vaccination dose on both antibody titers and neutralising potency towards SARS-CoV-2 B.1 and VoC isolates, often various vaccination regimens including heterologous vector-based/mRNA regimens were pooled in cohorts (14) or vaccine dosages not provided (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is, to our knowledge, the only study examining the longitudinal humoral and cellular immune response towards the most recent SARS-CoV-2 isolates in haemodiaylsis patients after administration of consistent vaccination regimens starting with a triple dose of BNT162b2 followed by a fourth full-dose of mRNA-1273. Whilst other studies principally support the beneficial impact of a fourth vaccination dose on both antibody titers and neutralising potency towards SARS-CoV-2 B.1 and VoC isolates, often various vaccination regimens including heterologous vector-based/mRNA regimens were pooled in cohorts (14) or vaccine dosages not provided (13).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported improved SARS-CoV-2 humoral and cellular responses not only towards the original SARS-CoV-2 B.1 isolate but also Delta and Omicron VoC after a fourth vaccination in haemodialysis patients receiving either mRNA vaccines or vector-based formulations in combination with mRNA vaccines (13)(14)(15). However, targeted data on the most efficient dosing and vaccination scheme or even predictors of vaccination success in haemodialysis patients at-risk of severe COVID-19 and its associated mortality is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Our study is, to our knowledge, the only study examining the longitudinal humoral and cellular immune response towards the most recent SARS-CoV-2 isolates in haemodiaylsis patients after administration of consistent vaccination regimens starting with a triple dose of BNT162b2 followed by a fourth fulldose of mRNA-1273. Whilst other studies principally support the beneficial impact of a fourth vaccination dose on both antibody titers and neutralizing potency towards SARS-CoV-2 B.1 and VoC isolates, often various vaccination regimens including heterologous vector-based/mRNA regimens were pooled in cohorts (14) or vaccine dosages not provided (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported an improved SARS-CoV-2 humoral and cellular responses not only towards the original SARS-CoV-2 B.1 isolate but also Delta and Omicron VoC after a fourth vaccination in haemodialysis patients receiving either mRNA vaccines or vector-based formulations in combination with mRNA vaccines (13)(14)(15). However, targeted data on the most efficient dosing and vaccination scheme or even predictors of vaccination success in haemodialysis patients at-risk of severe COVID-19 and its associated mortality is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The study adheres to the Declaration of Helsinki. It was approved by the Medical Ethics Committee of the Klinikum Rechts der Isar of the Technical University of Munich (approval number 163/21 S-SR, 19th March 2021) and registered at the Paul Ehrlich Institute (NIS592) (25).…”
Section: Methodsmentioning
confidence: 99%